Breeding possibilities of pheasants (p. colchicus) in intensive conditions and cold climatic zone; i. egg production and hatchability characteristics - Orhan Çetin; Cafer Tepeli; Kemal Kırıkçı (Eurasian Journal of Veterinary Sciences)
This study has been carried out for breeding possibilities of Pheasants were mated one male with live female in cages. Following the onset of lighting programme. the first egg was laid in 31 days. Average values off egg production, percent egg production, egg weight, fertility, hatchability, hatchability of fertil eggs were determined as; 68.30. 39.37 %, 33.36 g, 81.63 %, 62.03 % and 75.99 % respectively. Egg production period of pheasants were determined as 173 days. Date of first oviposition were realized 41 weeks age. Average body weight of male and female adult pheasants (41 weeks age) were found as; 1430.83 g and 1214.62 g respectively. As a result of this study its considered that the pheasants will be able to breed in farm conditions in Middle Anatolia If optimal environmental conditions are provided. Further researches on improvement of production characteristics of pheasants should be carried out for the development of production industry of this species in Türkiye.